2017
DOI: 10.1002/cplu.201700049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Functionalization Process on the Colloidal, Magnetic Resonance Imaging, and Bioelimination Properties of Mono‐ or Bisphosphonate‐Anchored Dendronized Iron Oxide Nanoparticles

Abstract: The functionalization process of iron oxide nanoparticles (NPs) is a major step and has to ensure a small particle size distribution (below 100 nm) and to preserve good magnetic properties suitable for in vivo applications. Two functionalization processes are here compared to coat iron oxide NPs, synthesized by thermal decomposition, with dendron molecules bearing either a mono‐ or a bisphosphonate anchoring group. The two processes are direct ligand exchange and the simultaneous ligand exchange and phase tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 47 publications
(149 reference statements)
3
26
0
Order By: Relevance
“…[47][48][49][50] IONPs were transferred to aqueous media following a well-established protocol. 49,51,52 The resulting IONPs were coated with dendrons bearing phosphonic acid tweezers and three PEG chains for biocompatibility to ensure a strong coupling to the IONP surface. Finally, two commercial IONPs were used: i) FluidMag-CT (FM-CT; product number: 4122-1) are manufactured by Chemicell GmbH (Berlin, Germany); ii) HyperMAG C (LRL) are manufactured by Liquids Research Limited (Bangor, United Kingdom).…”
Section: Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…[47][48][49][50] IONPs were transferred to aqueous media following a well-established protocol. 49,51,52 The resulting IONPs were coated with dendrons bearing phosphonic acid tweezers and three PEG chains for biocompatibility to ensure a strong coupling to the IONP surface. Finally, two commercial IONPs were used: i) FluidMag-CT (FM-CT; product number: 4122-1) are manufactured by Chemicell GmbH (Berlin, Germany); ii) HyperMAG C (LRL) are manufactured by Liquids Research Limited (Bangor, United Kingdom).…”
Section: Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…Syntheses of iron oxide NPs with various shapes and coated with oleic acid (OA) was achieved according to previously reported procedures [47]. Also, the synthesis procedure of the dendron molecule can be found in [18,34,50]. Functionalization of the NPs by the dendron molecules is performed through a direct grafting process.…”
Section: Dendronized Nps Preparationmentioning
confidence: 99%
“…avoiding RES uptake. Recent in vitro and in vivo results with 10 nm sized spherical NPs confirmed that they do not internalize in cells and accumulate in organs after IV injection [17,18,24].…”
Section: Introductionmentioning
confidence: 96%
“…Phosphonates and bis-phosphonates were already used as chain end-groups for IONP pegylation. 17 In previous reports studying stealth IONPs in vitro or in vivo, phosphonic acid anchors were rather grafted along the polymer backbone, either in a block structure with PEG 18,19 or as a statistical copolymer with PEG sidechains. 20 Other types of anchoring moieties are also used for IONP pegylation, like nitrodopamine 21 or silanes 22,23 .…”
Section: Introductionmentioning
confidence: 99%